METODE MENGAJAR BERVARIASI DAN UPAYA PENGEMBANGANNYA DALAM MENINGKATKAN HASIL BELAJAR PADA BIDANG STUDI PENDIDIKAN AGAMA ISLAM DI SMA MUHAMMADIYAH 11 PADANGSIDIMPUAN - HERMAN Herman Pelangi (Al-Muaddib : Jurnal Ilmu-Ilmu Sosial & Keislaman, 2018)
This paper aims to: 1) to find out how the implementation of the development of teaching methods varies in SMA Muhammadiyah 11 Padangsidimpuan, 2) to find out whether there is an increase in student learning through the development of varied teaching methods on learning Islamic religious education in SMA Muhammadiyah 11 Padangsidimpuan.Untuk achieve goals this author uses qualitative research. Data were collected through observation and interview techniques. Students are assessed based on observation and interview guidelines conducted by the author by collaborating and observing students' attitudes during the learning progress, while interviews are assessed based on the answers to questions with teachers and students. Data analysis is done through data reduction, data presentation and conclude. The results obtained through the technique is an increase in learning of Islamic Religious Education through the development of varied teaching methods that can be seen that before implementing the learning, teachers first make learning planning to create an atmosphere of learning in accordance with the purpose of learning and implementation of learning evaluation. Thus it can be concluded that the development of varied teaching methods can improve the learning of Islamic Religious Education students in class XI1 in SMA Muhammadiyah 11 Padangsidimpuan. Keywords: Teaching methods, varied, effort, development, learning outcomes, field of study, Islamic religious education.